Disrupting Consensus: A Discourse Theoretical Reading of Gen Z Protests in Indonesia - Irfai Afham; Yesi Mustika (Talenta Publisher, 2026)
This article examines the recent wave of Gen Z protests in Indonesia through the lens of discourse theory, drawing particularly on Laclau and Mouffe’s concepts of hegemony, antagonism, and agonistic pluralism. Furthermore, young activists disrupt elite-driven consensus politics by rearticulating the meanings of democracy, justice, and representation, thereby exposing the fragility of hegemonic orders. Hence, fueled by grievances over inequality, corruption, and the rising cost of living, these protests highlight how digital activism, memes, and popular culture have become central repertoires of contention, mobilizing solidarity and creating new political frontiers against both gerontocracy and authoritarian populism. At the same time, Derrida’s notion of deconstruction helps illuminate how Gen Z challenges generational hierarchies and destabilizes taken-for-granted norms, while Foucault’s insights into power/knowledge clarify how digital discourse functions simultaneously as a tool of empowerment and an object of surveillance. Therefore, the interplay of creativity and vulnerability in youth activism demonstrates the double-edged nature of social media, which amplifies dissent but also invites repression through censorship, disinformation, and surveillance. Moreover, by situating these mobilizations within broader debates on civil society and democratic contestation, the article argues that Gen Z’s disruptive practices contribute to the repoliticization of Indonesia’s public sphere and the sustenance of democratic conflict as a vital dimension of pluralism. However, the ability of these movements to transform episodic bursts of dissent into enduring institutional reforms remains uncertain. Ultimately, the study highlights a generational reconfiguration of democratic struggle in post-Reformasi Indonesia, where discourse, hegemony, and legitimacy are persistently contested.